Ligation mediated fluorescent labeling of DNA sequencing primers. - Jang, G Y (1997)
Automated DNA sequencing utilizing fluorescently labeled primers is a proven methodology for generating quality sequence data. However, for directed primer walking strategies this necessitates synthesis and labeling of a unique primer for each sequencing reaction. Here, we describe a rapid ligation-based method of generating labeled sequencing primers. An unlabeled 5'-phosphorylated sequencing primer is ligated to a fluorescent oligonucleotide by use of a bridge primer which is complementary to portions of the previous two oligonucleotides, thus aligning them properly for ligation. The resulting fluorescent hybrid primer can be utilized directly in cycle sequencing reactions without any prior purification.